First molecular verification of Dixonius vietnamensis Das, 2004 (Squamata: Gekkonidae) with the description of a new species from Vinh Cuu Nature Reserve, Dong Nai Province, Vietnam - Ziegler, Thomas; Botov, Andreas; Nguyen, Tao Thien; Bauer, Aaron M.; Brennan, Ian G.; Ngo, Hanh Thi; Nguyen, Truong Quang (Zootaxa, 2016)
Based on near-topotypic specimens of Dixonius vietnamensis from Khanh Hoa Province in southern Vietnam genetic analyses showed that the recently described D. taoi is sister to D. vietnamensis and several separate forms exist which previously have been misidentified as D. vietnamensis and D. siamensis. The Dixonius population from Vinh Cuu Nature Reserve, Dong Nai Province, Vietnam, represents an undescribed species. Dixonius minhlei sp. nov. can be distinguished from its congeners based on the following diagnostic characters: small size (up to 47.5 mm SVL); 7–9 supralabials; 14–15 rows of keeled tubercles on dorsum; 20–23 ventral scale rows; 7 or 8 precloacal pores in males; a canthal stripe running from rostrum through the eye and terminating at back of head; lateral second pair of postmentals maximum one quarter the size of first pair; dorsum olive gray with more or less discernible brownish olive blotches. This is the sixth species of Dixonius known to occur in Vietnam.